2018
DOI: 10.1111/eth.12754
|View full text |Cite
|
Sign up to set email alerts
|

The oddity effect drives prey choice but not necessarily attack time

Abstract: The tendency of predators to preferentially attack phenotypically odd prey in groups (the oddity effect) is a clear example of how predator cognition can impact behaviour and morphology in prey. Through targeting phenotypically odd prey, predators are thought to avoid the cognitive constraints that delay and limit the success of attacks on homogenous prey groups (the confusion effect). In addition to influencing which prey a predator will attack, the confusion and oddity effects would also predict that attacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
(85 reference statements)
2
17
0
Order By: Relevance
“…By comparing both which prey are attacked and when these attacks are made, we demonstrate, however, that the choice of which prey to attack has the greater effect on how attacks are distributed between different prey positions. This is consistent with other studies, where the effect of prey variation was most evident in the choice of which prey to attack rather than in other predator behaviors, such as the time taken to attack (17,26,39). Together, these studies suggest that the choice of which prey to attack is the most sensitive aspect of predator behavior affected by variation in prey.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By comparing both which prey are attacked and when these attacks are made, we demonstrate, however, that the choice of which prey to attack has the greater effect on how attacks are distributed between different prey positions. This is consistent with other studies, where the effect of prey variation was most evident in the choice of which prey to attack rather than in other predator behaviors, such as the time taken to attack (17,26,39). Together, these studies suggest that the choice of which prey to attack is the most sensitive aspect of predator behavior affected by variation in prey.…”
Section: Discussionsupporting
confidence: 91%
“…Analysis of the predator's timing of when to attack rather than which prey to attack revealed nonrandom timing, as attacks were more likely when solitary prey were more frequent. In general, studies attempting to understand how prey traits affect predatory behavior have focused on decisions by predators of which prey to attack, the time taken to attack, and whether to attack (17,18,39). Very few studies have explored when predators attack based on how prey traits vary over time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated oddity effects in vertebrates and invertebrates using differently coloured prey items (e.g., Landeau & Terborgh, 1986;Penry-Williams et al, 2018;Ohguchi, 1978). In contrast, such effects are less clear when body size is the odd criterion within a group.…”
Section: Discussionmentioning
confidence: 95%
“…Daphnids are freshwater planktonic crustaceans (McCauley & Murdoch, 1987;McCauley, Murdoch, Nisbet, & Gurney, 1990), with several species regularly co-occurring in the same habitat (Hanski & Ranta, 1983;Pajunen & Pajunen, 2003). They represent an important food source for many fish species (Brooks & Dodson, 1965), with odd-coloured individuals facing a higher risk of predation (Ohguchi, 1978;Penry-Williams, Ioannou, & Taylor, 2018;Rodgers et al, 2013). Daphnids are well known for their impressive phenotypic plasticity and morphological responses to changes in predation risk (Beckerman, Rodgers, & Dennis, 2010;Laforsch & Tollrian, 2004;Tollrian, 1995).…”
mentioning
confidence: 99%
“…Predation by native species could reduce, or at least slow down, invasions by non-native species (Zuharah & Lester 2010; Zuharah & Lester 2011) because they may not be able to recognise native predators (Sih et al 2010), but also because their different appearance could make them easier to detect, or make them more attractive, to native predators (the ‘oddity prey effect’, (Penry□Williams et al 2018). For example, killer shrimp are typically larger than native freshwater gammarids (Devin et al 2003), and this might make it easier for visual predators to detect them.…”
Section: Discussionmentioning
confidence: 99%